Multilayer dielectric coated Fabry Perot spectral beam combiner for high power, narrowband, widely tunable laser applications. (August 2020) - Rana, Paramjit; Mukherjee, C.; Mishra, S.K.; Kamparath, Rajiv; Sahoo, S.P.; Mukherjee, Jaya; Rawat, V.S.
Highlights: Multilayer dielectric coated F-P spectral beam combiner demonstrated. This device proved to be efficient for closer wavelength (<10 nm) combination. F-P filter combined the beams along with filtering out the ASE. A tuning mechanism to handle wide wavelength tunability was established. This scheme has promising applications in DIAL systems. Abstract: Spectral beam combination of tunable laser beams demonstrated, using a multilayer dielectric coated single cavity Fabry Perot (FP) filter. A stack of 19 layers using TiO2 and SiO2 was optimally designed and fabricated using an electron beam evaporation technique. This filter was characterized for transmission spectrum, surface morphology and laser induced damage threshold. The sharp transmission spectrum facilitated the spectral combination of closer wavelengths (<10 nm) around 632.8 nm. This filter was utilized as an efficient spectral beam combiner as well as an amplified spontaneous emission (ASE) filter for the transmitting wavelength. This study finds direct application for tunable, multi-wavelength laser-based differential absorption lidar (DIAL) and atmospheric remote sensing applications. The application of this device was successfully demonstrated to spectrally combine high power, tunable copper vapor laser pumped dye laser beams. A mechanism to tune the FP transmission profile along with laser beam tunability was established.